1991
DOI: 10.1111/j.1348-0421.1991.tb01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey for Lyme Disease in Sika Deer (Cervus nippon yesoensis) by Enzyme‐Linked Immunosorbent Assay (ELISA)

Abstract: Seventy-six wild sika deer (Cervus nippon _yesoensis) from areas endemic for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The percentage was higher than 25% in another endemic area of Hokkaido (12). In the study site, sika deer escaped extermination by a hair's breadth.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The percentage was higher than 25% in another endemic area of Hokkaido (12). In the study site, sika deer escaped extermination by a hair's breadth.…”
Section: Discussionmentioning
confidence: 95%
“…Wild animals are important as reservoirs or susceptible hosts for B. burgdorferi (1,7,27). From serological surveys, it is clear that various mammalian hosts are infected with B. burgdorferi sensu lato in Japan (2,12,13). B. burgdorferi was isolated from the spleen of Apodemus speciosus (wild rodent) (30) and from a wild fox with systemic infection (11) in the Hokkaido region of Japan.…”
mentioning
confidence: 99%
“…In Japan, seroepidemiological studies of Lyme borreliosis have been carried out among humans, pets, and domestic animals. However, there is little information available concerning Japanese wild animals, with the exception of a study of wild sika deer (Cervus nippon yesoensis) reported by Isogai et al [6]; because it is difficult to collect samples from wild animals and there are few serological methods adaptable to the wide range of animal species. It was recently reported that protein G reacts to a wide range of animal species' immunoglobulins, and therefore it has been gradually introduced for use in serological assays [1,4,7].…”
mentioning
confidence: 99%
“…Our results indicate that Lyme borreliosis is prevalent in wild Japanese serows, and the positive rate (23%) is relatively higher than that in companion and domestic animals. In Hokkaido, Japan, Isogai et al [6] reported that the positive rate of sika deer with Lyme disease was 25.0%; thus, sika deer are assumed to be one important host. Furthermore, there have been many reports involving the serological surveillance of wild animals around the world [2,[9][10][11].…”
mentioning
confidence: 99%
“…The microorganism is transmitted by infected ixodid ticks to a broad range of vertebrates, including humans, mice, dogs, and deer (1,3,(11)(12)(13)23). In Japan, it has been reported only in humans (1,11), dogs (13), and Sika deer (12). Human infection in Japan with B. burgdorferi is often asymptomatic (11).…”
mentioning
confidence: 99%